Using Pull up Test on The Horizontal Bar for Measuring Short Anaerobic Capacity of Arm Muscles with the Indication of (Weight, Distance, Frequency) According to Power Equation - Alyasri, Hamed; Altay, Usama (Journal of Physical Education, 2008)
The aim of the research is to examine short anaerobic capacity of arm muscles using the indicators of weight, distance and frequency according to power equation as well as pull up test on horizontal bar for ten seconds. In addition to that it aims at identifying the relationship between the variables of the research and their contribution. It also aims at identifying the effect of those variables on the short anaerobic capacity. The researchers used the descriptive method. The subjects were (70) second year students of the college of physical education/ University of Baghdad. They were test with a pull up test on a horizontal bar for ten seconds and the power equation was applied. They depended on the variables of weigh, distance and frequency. The researchers concluded that horizontal bar pull up test can be used to measure short anaerobic capacity of arm muscles. Also the variables of the study had a great significance and contribution. Finally they both recommended using power equation for measuring short anaerobic capacity of arm muscles as well as making special standards of pull up test on horizontal bar using power equation.